Performance Analysis of Millimeter waves over FSO System under Fog Weather Conditions - Shakthi Murugan K H, Sumathi M (International Journal of Advanced Science and Technology, 2020)
Many research works have been oriented towards achieving higher data rates. Optical WirelessCommunication (OWC) has gained a lot of importance. Millimeter waves have been coupled with FreeSpace Optics (FSO) to yield higher data rates and error free communication. A Radio over-FSO (RoFSO) system is designed with two different channels, each carrying 5Gbps data rate which istransmitted over 60GHz radio signal, yielding better performance to be used in 5G communicationnetworks. The atmospheric turbulence in the form of fog is introduced and the system performance isstudied in terms of Bit Error Rate (BER).